2010
DOI: 10.1073/pnas.0909396107
|View full text |Cite
|
Sign up to set email alerts
|

Dual role of lignin in plant litter decomposition in terrestrial ecosystems

Abstract: Plant litter decomposition is a critical step in the formation of soil organic matter, the mineralization of organic nutrients, and the carbon balance in terrestrial ecosystems. Biotic decomposition in mesic ecosystems is generally negatively correlated with the concentration of lignin, a group of complex aromatic polymers present in plant cell walls that is recalcitrant to enzymatic degradation and serves as a structural barrier impeding microbial access to labile carbon compounds. Although photochemical mine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
337
2
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 401 publications
(369 citation statements)
references
References 47 publications
26
337
2
4
Order By: Relevance
“…1 C and D and Tables S3 and S4). In general, these results are quantitatively consistent with other studies that explored photodegradation of plant litter under field conditions (12,16,17,20) although the breadth of species evaluated here, which ranged from annual herbaceous species to conifer and angiosperm tree species, establishes a general pattern for the spectral dependence of photodegradation of plant litter in terrestrial ecosystems.…”
Section: Uv and Bg Radiation Significantly Promote Organic Mass Loss supporting
confidence: 91%
See 3 more Smart Citations
“…1 C and D and Tables S3 and S4). In general, these results are quantitatively consistent with other studies that explored photodegradation of plant litter under field conditions (12,16,17,20) although the breadth of species evaluated here, which ranged from annual herbaceous species to conifer and angiosperm tree species, establishes a general pattern for the spectral dependence of photodegradation of plant litter in terrestrial ecosystems.…”
Section: Uv and Bg Radiation Significantly Promote Organic Mass Loss supporting
confidence: 91%
“…First, whereas it has been demonstrated that litter mass loss is directly caused by exposure to solar radiation (12,17,20), we suggest that the principal and quantitatively most important effect of photodegradation on the global carbon cycle may be the facilitation of biotically mediated carbon turnover. We demonstrate here, with a direct comparison of direct photodegradation and biotic decomposition (Table S4), that biotic decomposition overall had a much larger effect on organic matter loss for the same species (range 4-65%) than the direct effect of photodegradation, which was generally small (range 1.5-4.5%) (Table S4).…”
Section: Exposure To Solar Radiation Strongly Enhances Subsequent Micmentioning
confidence: 74%
See 2 more Smart Citations
“…Nitrogen addition can enhance N availability and soil enzyme activity, thereby accelerating litter decomposition (Knorr et al 2005;Manning et al 2008). Lignin is a key factor in the regulation of litter decomposition, especially during the later decay stage (Austin and Ballaré 2010). Excessive N inputs have been demonstrated to suppress ligninolytic enzyme activity in the long term and correspondingly reduce litter decomposition (Fog 1988;Carreiro et al 2000;Thirukkumaran and Parkinson 2000;Hobbie et al 2012), although a few studies have found no evidence of negative effects (Hobbie et al 2006).…”
Section: Effects Of N Deposition and Management Practices On Litter Dmentioning
confidence: 99%